2015
DOI: 10.1615/jenvironpatholtoxicoloncol.2015012006
|View full text |Cite
|
Sign up to set email alerts
|

Lead Acetate-Induced Hepatoxicity in Wistar Rats: Possible Protective Role of Combination Therapy

Abstract: Experimental studies have shown that sulphur-containing antioxidants have beneficial effects against the detrimental properties of Pb. In the present study, we investigated the therapeutic potential of combined administration of N-acetyl cysteine (NAC; 50 mg/kg p.o.) and selenium (Se; 0.5 mg/kg p.o.) against lead acetate intoxication (Pb; 0.2% in water ad libitum) in a male rat model for 12 wk. The exposure of rats to lead acetate produced significant (P < 0.05) alterations in cytochrome P450 (CYP) activity, m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 0 publications
1
6
0
Order By: Relevance
“…Moreover, the liver is the body’s largest detoxification organ, a lot of detoxification enzymes, such as cysteine proteases, will be affected by lead. Previous studies have shown that lead exposure can cause oxidative damage in the liver by inhibiting the activities of antioxidant enzymes, decreasing the concentration of non-enzymatic antioxidants and increasing the concentration of reactive oxygen species [36,37,38]. Our results showed that lead acetate added to the drinking water for six weeks for mice resulted in severe histopathological changes in the liver tissue.…”
Section: Discussionsupporting
confidence: 47%
“…Moreover, the liver is the body’s largest detoxification organ, a lot of detoxification enzymes, such as cysteine proteases, will be affected by lead. Previous studies have shown that lead exposure can cause oxidative damage in the liver by inhibiting the activities of antioxidant enzymes, decreasing the concentration of non-enzymatic antioxidants and increasing the concentration of reactive oxygen species [36,37,38]. Our results showed that lead acetate added to the drinking water for six weeks for mice resulted in severe histopathological changes in the liver tissue.…”
Section: Discussionsupporting
confidence: 47%
“…In our study, we evaluated the effects of the ozone and selenium applications on alcoholic liver damage using histopathological analyses and assessment of serum AST and ALT levels. It has been reported in various studies that AST and ALT levels increase independently of the cause of the damage (19)(20)(21). It has also been reported that selenium application with N-acetylcysteine has a protective effect on lead and mercury toxicity (19,20), lowers ALT activity in thioacetamide-induced cirrhosis and AST and ALT in arsenic toxicity (21).…”
Section: Discussionmentioning
confidence: 98%
“…It has been reported in various studies that AST and ALT levels increase independently of the cause of the damage (19)(20)(21). It has also been reported that selenium application with N-acetylcysteine has a protective effect on lead and mercury toxicity (19,20), lowers ALT activity in thioacetamide-induced cirrhosis and AST and ALT in arsenic toxicity (21). In the case of alcohol, it is reported that ebselen, an organoselenium compound, reduces elevated ALT in rats treated with alcohol (22).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a neuroscientist in the Rural Environments Group noted that lead poisoning is, in fact, associated with changes in thyroid function, although a specific connection between lead toxicity and thyroid cancer has not been conclusively demonstrated. Lead poisoning is associated with a decrease in circulating levels of thyroid hormone distributor proteins in lab animals [18,19] and in the cerebral spinal fluid of humans [20], suggesting this as a possible mechanism by which lead poisoning may lead to an overgrowth of the thyroid gland. This insight contributed to the Rural Environments Group's determination that further investigations into the lead emissions from open burning at RAAP were warranted.…”
Section: University and Faculty Support Of Transdisciplinary Communitmentioning
confidence: 99%